Calculating Derivative – A quotient of a multiplication of polynoms and an exponential function – Exercise 6277


Find the derivative of the following function:


Final Answer

f'(x)=\frac{{(2x-3)}^4}{e^{3x^2+1}}\cdot (-12x^3+18x^2+12x-3)



Using Derivative formulas and the quotient rule in Derivative Rules, we get the derivative:

f'(x)=\frac{[{(2x-3)}^5+5x{(2x-3)}^4\cdot 2]\cdot e^{3x^2+1}-x{(2x-3)}^5\cdot 6x\cdot e^{3x^2+1}}{{(e^{3x^2+1})}^2}=

One can simplify the derivative:

=\frac{{(2x-3)}^4}{e^{3x^2+1}}\cdot [(2x-3)+10x-6x^2(2x-3)]=

=\frac{{(2x-3)}^4}{e^{3x^2+1}}\cdot (2x-3+10x-12x^3+18x^2)=

=\frac{{(2x-3)}^4}{e^{3x^2+1}}\cdot (-12x^3+18x^2+12x-3)

Have a question? Found a mistake? – Write a comment below!
Was it helpful? You can buy me a cup of coffee here, which will make me very happy and will help me upload more solutions! 

Share with Friends

Leave a Reply